ASIAN HAJJ ROUTES: THE REFLECTION OF HISTORY AND GEOGRAPHY - Ladjal, Tarek (Journal of Al-Tamaddun, 2013)
The rise of Islam in East and South-East Asia effectively marked a turning point in the political, cultural and economic history of the entire region. Changes that took place in this area were clearly reflected in activities of day to day life, particularly in the case of land and sea trips from and to these areas which were deeply influenced by the emersion of a new travelling destination; the Hajj (i.e., pilgrimage). In the past decades, these routes were only dedicated to trade but have lately become one of the most important Hajj routes in history due to the human factor. This paper aims at collecting the bits and pieces available on this subject matter to present a comprehensive historical and geographical image for these routes which were known as the ?Asian Hajj routes.? The paper also introduces relations between this area and Arabic countries before the era of Islam, as well as the Hajj land and sea routes to shed light on the civilization aspects of these routes. It also attempts to shed light on the realty and the reflections of the trade roads on the Hajj Routes and the impacts of the Hajj roads in shaping the Islamic identity in the Muslim society in China and the Malay world.